2020
DOI: 10.1111/jvim.15850
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility of echocardiographic indices of left atrial size in dogs with subclinical myxomatous mitral valve disease

Abstract: Background: Reliability of echocardiographic measurements of left atrial (LA) size, an important marker of disease severity, has not been reported in dogs with myxomatous mitral valve disease (MMVD). Objectives: To define and compare reliability of left atrial dimension/diameter (LAD), LAD indexed to aortic valve diameter (LAD/AoD), left atrium-to-aortic root ratio (LA/Ao), left atrial volume acquired from a right parasternal long-axis (LAV RPLx), and left apical view (LAV LAP) in dogs with subclinical MMVD. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 38 publications
1
8
1
Order By: Relevance
“…While data about repeatability and reproducibility are not available for LA APD5CH and LA area, in our study we found similar intraobserver ICCs for LA:Ao and LA APD , to what recently reported in another study, where measurements were performed by a trained diagnostic imaging resident on a selected group of healthy dogs [ 17 ]. The interobserver ICCs that we found in this study for LA:Ao and LA APD , are instead slightly higher than previously reported in both healthy dogs and dogs affected by myxomatous valvular degeneration, even though all the observers in these studies were reported to have received some training [ 17 , 22 ]. This is explained by the different forms of interobserver ICC.…”
Section: Discussioncontrasting
confidence: 84%
“…While data about repeatability and reproducibility are not available for LA APD5CH and LA area, in our study we found similar intraobserver ICCs for LA:Ao and LA APD , to what recently reported in another study, where measurements were performed by a trained diagnostic imaging resident on a selected group of healthy dogs [ 17 ]. The interobserver ICCs that we found in this study for LA:Ao and LA APD , are instead slightly higher than previously reported in both healthy dogs and dogs affected by myxomatous valvular degeneration, even though all the observers in these studies were reported to have received some training [ 17 , 22 ]. This is explained by the different forms of interobserver ICC.…”
Section: Discussioncontrasting
confidence: 84%
“…From a practical point of view, this also suggests that considering linear LA measurements only, may lead to an erroneous left heart evaluation, which will not be the case when using volumetric methods only. The high negative prognostic value of LA enlargement has been demonstrated in DMVD dogs [ 11 , 37 , 38 ], with LA volume being the strongest predictor of cardiac-related death, highly superior to all other parameters of LA size and function including LA/Ao ratios [ 43 , 44 ]. Therefore, as in human cardiology [ 45 ], LA volumetric quantification should the method of first choice for assessing LA size particularly to stratify ACVIM stage B dogs.…”
Section: Discussionmentioning
confidence: 99%
“…2 C, Additional file 1 ), and LA:AO had the highest correlation coefficient. Interestingly, LA:AO is a convenient and body size-independent measurement, and it is also a typical index for evaluating the size of LA of dogs with MMVD [ 8 , 23 ]. Thus, the turquoise module was used for subsequent analysis, because it is likely to correlate more closely correlated with cardiac remodeling.…”
Section: Discussionmentioning
confidence: 99%